Uma análise sobre o abastecimento de carne verde em Belém durante a intendência de Antônio Lemos (1897 - 1908) - SANTOS, Francimary Nascimento Da Silva (2019)
This article discusses an important facet of Belenian society in the early 20th century: the complex supply of green meat. The main focus of this analysis is the discussion of the dependence of cattle that were imported from neighboring states and republics of the platinum region as a guarantee of maintenance of the supply of this product in the markets of the capital. Another concern is to reflect on the intervention policies adopted by then-Mayor Antônio Lemos regarding the amount of animals that were slaughtered daily by the capital's dealers. With this, Lemos sought to balance the supply of this genre with demand. Thus, for the intendant, there would be no waste and would be an alternative for eventual supply crises. We believe in the thesis that there were crises in the supply, but not because of possible monopolies between the dealers. The short periods of absolute lack of green meat were due not only to the lack of livestock production in Paraense, but also to problems in the importation of this product, either from national regions or from the regions of the country. In addition to the periodicals, the messages of the governors and the reports of the Intendência de Belém were also used in this analysis.